Analisis Kesalahan dalam Menyelesaikan Soal Cerita Aritmatika Sosial Ditinjau dari Kemampuan Awal Siswa - Usman Mulbar; Alimuddin; Wa Ode NurRadhiah Ridjalu (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2022)
This study aims to determine the description of errors, types of errors, and the causes of errors made by students in solving social arithmetic story problems in terms of students’ initial abilities. The type of research us ed is dercriptive research. A total of 28 students of class VII became subjects in this stu dy. Data was collected using written tests and interviews . The collected data were analyzed quantitatively and qualitatively. The results showed that the percentage of errors from the largest to the smallest in a row is a problem with the concept of profit, purchase price, net weight, interest, discounts and taxes. The types of errors from the largest to the smallest percentages are errors in understanding the proble m, errors in completing mathematical models, errors in making mathematical models, and errors in writing the final answer to the questions. The causes of students errors are not understanding the meaning of the question, not mastering the concepts related to the problem, not mastering the steps in solving the problem, lacking mastery in the calculation process, unable to determine the next formula to solve the problem, making mistakes in the previous process, unable to write final answer, forgetting factor, and lack of practice working on the questions.